2010
DOI: 10.1007/s11249-010-9581-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fretting Fatigue of Cavitation Shotless Peened Ti–6Al–4V

Abstract: Fretting fatigue behavior of cavitation shotless peened titanium alloy, Ti-6Al-4V coupons was investigated using finite element method and a critical planebased multi-axial fatigue parameter. Cavitation shotless peening (CSP)-induced compressive residual stress, which was larger at the contact surface than its counterpart from the shot peening (SP). However, compressive residual stress decreased more sharply with distance from the contact surface in CSP than in SP. Analysis using a critical plane-based multi-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similar to clamping stress, compressive residual stress can also close up FF cracks in the early stages of FF crack propagation [45]. Therefore, the early FF crack propagation rate is significantly reduced by the induction of large compressive residual stress in the near-surface region after USRP treatment [46][47][48][49]. In summary, the compressive residual stress introduced by USRP treatment can improve the FF resistance of 300M steel.…”
Section: Fretting Fatigue Testmentioning
confidence: 98%
“…Similar to clamping stress, compressive residual stress can also close up FF cracks in the early stages of FF crack propagation [45]. Therefore, the early FF crack propagation rate is significantly reduced by the induction of large compressive residual stress in the near-surface region after USRP treatment [46][47][48][49]. In summary, the compressive residual stress introduced by USRP treatment can improve the FF resistance of 300M steel.…”
Section: Fretting Fatigue Testmentioning
confidence: 98%
“…As cavitation peening is shotless peening, as mentioned above, cavitation peening can introduce compressive residual stress and work hardening with less of an increase in surface roughness in comparison with other processes. Thus, cavitation peening improves the fretting fatigue properties and/or pitting resistance [37,[146][147][148]. The pressure distribution of individual cavitation impact was evaluated using a magnesium-oxide single crystal, and the authors concluded that the highly intense impact was applied to the center [149].…”
Section: Improvement In Triborogical Propertiesmentioning
confidence: 99%
“…As a result, cracks are initiated in the contact zone and the unexpected and/or premature failures under the fretting condition have been observed in many structural components at stress levels below the fatigue limit of materials. [1][2][3][4][5][6][7][8][9][10][11] One of the most common examples, where the mechanical failure is caused by fretting fatigue, is the dovetail joint of the blade and disk attachments in gas turbine engines.…”
Section: Introductionmentioning
confidence: 99%